Maternal near miss mortality: indication of maternal care - Ali, Maryam; Prabhakar, Manju; Sai Kuracha, Anjani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Maternal mortality is one of the important indicators used for the measurement of maternal health. To overcome this challenge, maternal near miss has been suggested as a compliment to maternal death. The prevalence of near miss is higher in developing countries and causes are similar to those of maternal mortality namely haemorrhage, hypertensive disorders, sepsis and obstructed labor. Reviewing near miss cases provide significant information about the delays in health seeking so that appropriate action is taken. It is useful in identifying health system failures and assessment of quality of maternal health-care. Certain maternal near miss indicators have been suggested to evaluate the quality of care. The near miss approach will be an important tool in evaluation and assessment of the newer strategies for improving maternal health. Here we are presenting case series of near miss mortality cases reported in Muzaffarnagar medical college.